2014
DOI: 10.1111/micc.12077
|View full text |Cite
|
Sign up to set email alerts
|

Role of Insulin and Adenosine in the Human Placenta Microvascular and Macrovascular Endothelial Cell Dysfunction in Gestational Diabetes Mellitus

Abstract: Microvascular and macrovascular endothelial function maintains vascular reactivity. Several diseases alter endothelial function, including hypertension, obesity, and diabetes mellitus. In addition, micro- and macrovascular endothelial dysfunction is documented in GDM with serious consequences for the growing fetus. Increased l-arginine uptake via hCAT-1 and NO synthesis by eNOS is associated with GDM. These alterations are paralleled by activation of purinergic receptors and increased umbilical vein, but not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 98 publications
(276 reference statements)
1
52
0
3
Order By: Relevance
“…15,19,20 Reduced expression and activity of hENT1 is known to lead to extracellular accumulation of adenosine in HUVECs primary cultures, 19 and inhibition of hENT1 increases the dilation of human umbilical vein rings. 18 Our results show that v i and overall adenosine transport was reduced in HUVECs from spGWG, suggesting altered membrane transport mechanisms mediating the removal of extracellular adenosine.…”
Section: Discussionmentioning
confidence: 99%
“…15,19,20 Reduced expression and activity of hENT1 is known to lead to extracellular accumulation of adenosine in HUVECs primary cultures, 19 and inhibition of hENT1 increases the dilation of human umbilical vein rings. 18 Our results show that v i and overall adenosine transport was reduced in HUVECs from spGWG, suggesting altered membrane transport mechanisms mediating the removal of extracellular adenosine.…”
Section: Discussionmentioning
confidence: 99%
“…In HUVECs from GDM or incubated with high concentration of D -glucose, there is high synthesis of NO (Sobrevia et al, 1995), related with high expression of the main L -arginine transporter: hCAT-1 (González et al, 2004, 2011; Guzmán-Gutiérrez et al, 2014). L -Arginine is the substrate for NO synthesis by eNOS (Alderton et al, 2003) and the transport of L -arginine is essential for NO synthesis in the endothelium (Shin et al, 2011).…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…Recent studies have shown the altered expression of IRs in the fetoplacental endothelium of GDM women, leading to abnormal fetal endothelium function [24], even when GDM is treated with diet containing normal levels of glucose. Nevertheless, insulin treatment was seen to restore IR expression in these patients leading to normal endothelial function and a normal newborn [25].…”
Section: Functions Of Insulin Within the Placentamentioning
confidence: 99%